Exploring multisensory home office design in virtual reality: Effects on task performance, heart rate, and emotion - Mengxin Li; Nayeon Kim (Acta Psychologica)
The integration of virtual reality (VR) and multisensory experiences offers a novel approach to enhancing workspace design, particularly for home office environments. This preliminary study examines the effects of visual and olfactory stimuli in a VR-simulated smart home environment on presence, task performance, heart rate, and mood. Sensory conditions, including visual, olfactory, and combined stimuli, were controlled in an experiment with 60 participants to assess both physiological and psychological responses. Task performance was measured through cognitive tests, while heart rate and mood states were monitored using a heart rate sensor and the Positive and Negative Affect Schedule (PANAS), respectively. Statistical results showed that the sense of presence provided by VR and specific conditions—such as visual stimuli (e.g., intelligent lighting systems)—effectively enhanced work efficiency, with task performance under visual stimuli significantly outperforming that under olfactory stimuli (e.g., peppermint scent). However, these sensory stimuli did not significantly affect heart rate or emotions. Our findings underscore the potential of sensory design to improve task performance and highlight the importance of the sensory environment in designing home offices, suggesting that sensory stimuli can enhance work efficiency in remote or virtual work settings.